Cyclo-(Phe-Tyr) as a novel cyclic dipeptide compound alleviates ischemic/reperfusion brain injury via JUNB/JNK/NF-κB and SOX5/PI3K/AKT pathways. (June 2022) - Cai, Jiale; Liang, Jiayin; Zhang, Yutong; Shen, Lin; Lin, Huiting; Hu, Tao; Zhan, Sikai; Xie, Meixia; Liang, Shengwang; Xian, Minghua; Wang, Shumei
Abstract: Ischemic/reperfusion (IR) can cause adverse reactions including apoptosis, oxidative stress, and inflammation, but the existing therapeutic strategies have been limited. Moreover, the regulation of microglia plays an important role in brain injury after reperfusion. Hence, it is imperative to find new and effective drugs for modulating microglia to treat IR brain injury. Cyclic peptide compound cyclo-(Phe-Tyr) (Sparganin C, SC) is a compound isolated from Sparganii Rhizoma . However, the protective effects of SC on the central nervous system are rather unclear. In an attempt to elucidate the protective effects and mechanism of SC on cerebral damage induced by the IR, we used a middle cerebral artery occlusion reperfusion (MCAO/R) model in rats and discovered that SC significantly decreased the size of cerebral infarcts, improved neurological scores, and blocked inflammatory and oxidative factor release. Using RNA-Seq and metabolomics association analyses, SC was shown to have a protective impact through the JUNB and SOX5-related pathways. Metabolomic analysis revealed twenty-eight differentially expressed biomarkers. In addition, the detection of SC content in brain tissue using LC/MS revealed that SC had blood-brain barrier penetration. To investigate the mechanism, we established an in vitro BV2 cell oxygen-glucose deprivation/reperfusion (OGD/R) model and used siRNA as well as an inhibitor. The protective effects of SC were dependent on the JUNB and SOX5 to inhibit inflammation and apoptosis in microglia. Our findings revealed for the first that SC against IR injury by reducing inflammation and apoptosis while simultaneously acting as potential therapeutic lead compound for ischemic stroke. Graphical Abstract: ga1